Parlamentskii chas . Parlamentskii chas . Parliamentary Hour . Парламентский час - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. The guests of the program express their opinions on the May demonstrations. Featured in the program: Abdulatipov, Ramazan Gadzhimuradovich (Chairman of the Council of Nationalities of the Supreme Council of Russian Federation); Kara-Murza, Sergei Georgievich (Scientist) Выступление участников передачи по поводу первомайских событий. В программе участвуют: Абдулатипов, Рамазан Гаджимурадович (Председатель Совета Национальностей Верховного Совета РСФСР); Кара-Мурза, Сергей Георгиевич (Ученый)